The Influence of Brand Image and Perceived Value on Purchase Intention (A Case Study on Sensodyne Toothpaste Brand in Sanggar District) - Asmul Fauzi; Yeye Suhaety; Fahrul Mauzu (Jurnal Strategi dan Inovasi Bisnis, 2026)
Background: Despite Sensodyne's claim as the number one sensitive toothpaste brand globally and in Indonesia, its purchase intention in Sanggar District remains relatively low. This phenomenon highlights an empirical gap between Sensodyne's global market leadership and the local market reality, which is heavily dominated by conventional brands. Furthermore, a theoretical gap exists due to inconsistencies in previous studies regarding the significance of brand image and perceived value on purchase intention. Purpose: This study aims to examine and explain the partial and simultaneous effects of brand image and perceived value on the purchase intention of Sensodyne toothpaste in Sanggar District. Methods: The research utilized a quantitative design with a causal associative approach. Data were gathered through questionnaires distributed to a sample of 100 respondents, selected via non-probability accidental sampling. The data were then analyzed using multiple linear regression. Results: The analysis revealed that brand image and perceived value partially have a positive and significant effect on purchase intention, with significance values of 0.000 and 0.025 respectively. Simultaneously, both variables significantly influence purchase intention with a significance value of 0.000. The coefficient of determination indicates that these two variables explain 69.6% of the variance in purchase intention. Conclusion: Brand image and perceived value are proven to positively and significantly influence consumer purchase intention both partially and simultaneously. The synergy between a strong brand reputation and the calculation of functional benefits effectively breaks the dominance of conventional brands, firmly supporting the Theory of Reasoned Action. Keywords: Brand Image; Perceived Value; Purchase Intention.